2022
DOI: 10.3390/ijerph19031027
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Non-Grain Production Based on Cultivated Land Multifunction Assessment

Abstract: The control of non-grain production (NGP) has become a great challenge for cultivated land protection in China in recent years. A control method for NGP that can coordinate the conflicts between cultivated land protection and farmers’ interest is urgently needed. Taking Tongxiang City as an example, this research proposed a solution for the control and management of NGP based on cultivated land multifunctional assessment. The GIS and AHP approach were used to assess production function via a comprehensive eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Finally, we took the village as the unit to analyze the spatial aggregation of abandoned farmland. On the basis of high data accuracy, we retained more details of the spatial pattern, which was more conducive to the detailed analysis of the spatial distribution characteristics of farmland abandonment (Su 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we took the village as the unit to analyze the spatial aggregation of abandoned farmland. On the basis of high data accuracy, we retained more details of the spatial pattern, which was more conducive to the detailed analysis of the spatial distribution characteristics of farmland abandonment (Su 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…After referring to the previous relevant researches (Gu 2013 ; Su 2020 ) and the consistency and availability of data accuracy, this study selected four potential indicators that affect the farmland abandonment: geography, proximity, distance, and policy, as shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the extent of the development of non-grain production in China, extant studies have shown that the phenomenon of non-grain production is becoming more and more serious, with more serious non-grain production in South, Northwest, Southwest, and Central China [ 8 , 16 ]. In terms of the mechanisms driving the phenomenon of non-grain production, some scholars have explored the analysis from the perspectives of cost and benefit [ 17 , 18 ], agricultural land transfer [ 19 ], industrial and commercial capital [ 20 ], policy understanding [ 21 ], farm household characteristics [ 22 ], labor transfer [ 23 ], cultivated land rental [ 24 ], and local government behavior [ 25 ]. Rising costs and declining returns of grain production [ 26 ], increased economic efficiency of non-grain economic crops [ 27 , 28 ], and dislocated government regulation [ 29 ] are important factors contributing to the serious phenomenon of non-grain production.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers are primarily concerned with the connotation and protection of multi-function cultivated land, the development of evaluation systems and multifunction evaluation, the study of time-space difference and driving mechanism, multi-function categorization and zoning, and so on [ 19 , 20 ]. In terms of multifunction measurement of cultivated land, the comprehensive evaluation method of indicators [ 10 , 21 ], material quality evaluation method [ 20 , 22 ], value evaluation method [ 23 , 24 ], and other methods are used. At the national [ 9 , 25 ], provincial [ 26 ], municipal [ 27 ], county [ 10 , 28 ], village [ 29 , 30 ], and grid levels [ 31 ], the multi-functional evaluation and zoning of cultivated land are investigated using the methods of full arrangement polygons [ 32 ], spatial autocorrelation [ 33 ], coupling coordination degree modeling [ 5 , 34 ], and Spearman level correlation coefficients [ 35 ].…”
Section: Introductionmentioning
confidence: 99%